Advances in production management systems : towards smart and digital manufacturing : IFIP WG 5. 7 International Conference, APMS 2020, Novi Sad, Serbia, August 30-September 3, 2020, Proceedings.: towards smart and digital manufacturing : IFIP WG 5. 7 International Conference, APMS 2020, Novi Sad, Serbia, August 30-September 3, 2020, Proceedings. Part II ([2020]) - Unknown
No abstract available